2022
DOI: 10.2186/jpr.jpr_d_22_00150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hollow structures added by selective laser sintering on the mechanical properties of Co-Cr alloy

Abstract: The inner lattice structures were added to the stem of an artificial femoral joint to obtain optimal mechanical properties similar to those of cortical bone in orthopedics. Consequently, the elastic modulus was successfully reduced to one-fifth of that of conventional implants [15]. SLS technology enables the addition of inner structures, unlike conventional processes, leading to localized changes in mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The internally integrated hollow structures can decrease the mass of the additively manufactured objects due to the apparent reduction in density, consequently reducing the cost and period of the printing procedure. 30 31 These results are consistent with previous studies that confirmed a significant mass reduction when hollow structures are incorporated inside the printed object relative to the reduction in density of the item. 32 33 …”
Section: Discussionsupporting
confidence: 91%
“…The internally integrated hollow structures can decrease the mass of the additively manufactured objects due to the apparent reduction in density, consequently reducing the cost and period of the printing procedure. 30 31 These results are consistent with previous studies that confirmed a significant mass reduction when hollow structures are incorporated inside the printed object relative to the reduction in density of the item. 32 33 …”
Section: Discussionsupporting
confidence: 91%